2015
DOI: 10.1007/s00445-014-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

Kawah Ijen volcanic activity: a review

Abstract: Kawah Ijen is a composite volcano located at the easternmost part of Java island in Indonesia and hosts the largest natural acidic lake in the world. We have gathered all available historical reports on Kawah Ijen's activity since 1770 with the purpose of reviewing the temporal evolution of its activity. Most of these observations and studies have been conducted from a geochemical perspective and in punctuated scientific campaigns. Starting in 1991, the seismic activity and a set of volcanic lake parameters be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 32 publications
(83 reference statements)
1
89
0
Order By: Relevance
“…Some of the early history of exploration of the volcano was covered by Caudron et al (2015), from which this summary of the recent history of Kawah Ijen is abstracted. Colonial visitors described the lake as early as 1789, and sulfur from the crater was used for the manufacture of gunpowder in the late 18th Century.…”
Section: Eruptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the early history of exploration of the volcano was covered by Caudron et al (2015), from which this summary of the recent history of Kawah Ijen is abstracted. Colonial visitors described the lake as early as 1789, and sulfur from the crater was used for the manufacture of gunpowder in the late 18th Century.…”
Section: Eruptionmentioning
confidence: 99%
“…Presumably, this final burst provided the phreatomagmatic debris found coating the surface of the entire Kawah Ijen crater and deposited at the top of the lahar sediments found in the drainage of the Banyu Pahit. Caudron et al (2015) concluded that the total erupted volume far exceeded any difference in crater size before and after 1817, and that a significant volume must therefore have erupted as magma.…”
Section: Eruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The processes have been described by Caudron et al [29]. Post caldera volcanic centers can be divided into two groups: Intra Caldera (IC) and Caldera Rim (CR) [27].…”
Section: Introductionmentioning
confidence: 99%